ICT Solutions in the D-Sys-Com Research: Analysis of the Needs and Attitudes of the Frail Elderly Person - Pinnelli, Stefania (Frontiers in Robotics and AI, 2022)
The introduction and use of innovative technological devices to support the aging of frail elderly people does not necessarily correspond to an improvement in people's quality of life. The strong technical curvature resulting from the use of telemedicine models often highlights limits in the usability of technologies in responding to the real needs of users. The theoretical framework of Special Pedagogy allows the assumption of the bio-psycho-social perspective and the constructs of quality of life and participation and opens up to inclusive logics that implement a profound and questioning reflection on all contexts of life, with the goal of exposing the set of disabling processes and indicating a valid support in the use of technological resources. The contribution, retracing the research phases of the Data System Platform for Smart Communities project, (project admitted for funding in the Innolabs 2018-2019 call), completed in 2020, presents the results of the analysis of the needs of strategic stakeholders and the results of the detection of expectations, attitudes and degree of satisfaction and trust towards telemedicine devices by frail elderly people.